UJI TARIK PADA TIANG UNTUK PENENTUAN MODULUS GESEK TIANG (k1) - , ANDIKANOZA PRADIPTIYA, Dr. Ir. Hary Christady Hardiyatmo, M.Eng., DEA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Shaft resistance of tension piles will be fully mobilized at certain displacement. Some structures impose limits to the displacement of piles with a relatively small value in order not to cause damage. Therefore, it is necessary to know the behavior of pile resistance reaction against load that works in every displacement that is shown by pile friction modulus (kt). The study was conducted using the model of single pile made of concrete with a length of 0,2 m, 0,3 m, 0,4 m and each diameter 0,02 m, 0,03 m, 0,04 m. The model pile jacked in clay and sand that has been compacted in a separate test and then given uplift load refers to the ASTM D3689-07 procedure E. Pile friction modulus (kt) is determined by mobilized unit shaft resistance (Rs) and pile displacement ( ) relationship. The results showed that the value of kt tends to decrease with increasing value of . kt of pile on clay is larger about 200% to 500% from pile on sand because the clay tends to give cohesive effect to the pile. Rs that is counted from kt can only approach the value of Rs observations so that requires further consideration to design application.